Haemolytic and immunoadjuvant effect of Butea frondosa on the immune response to hepatitis B vaccine containing surface antigen in mice - Amit Gupta; Sushama R Chaphalkar (Shahrekord University of Medical Sciences, 2016)
Introduction: Immunological adjuvants derived from various synthetic micro-organisms or from medicinal plant products enhance specific immune responses against vaccine antigens. Immunological studies have already done pertaining to identify compounds from medicinal plant metabolites that are suitable for vaccine formulation. In this study, aqueous leave extracts of Butea frondosa were selected to evaluate their haemolytic activity and immunoadjuvant effects. Methods: For this study, immunoadjuvant activity was investigated ex vivo in mice model based studies using splenocyte proliferation assay and also measured IgG titre in cell culture supernatant (using indirect ELISA). Swiss mice were immunized subcutaneously with specific protein antigen i.e. hepatitis B vaccine containing surface antigen (HBsAg, 20 μg/mL; 10 μl) on day 0 and collected the spleen cells on day 4 and proceeded for proliferation assay of variable doses of aqueous leaves extracts of Butea frondosa (0.5-30 mg/ml; 50 μl) along with hepatitis B surface antigen (HBsAg) (challenging dose; 20 μg/mL; 10 μl) and also estimated the antibody (IgG) titre in splenocyte cell culture supernatant including determination of its haemolytic activity in human whole blood samples. Results: The results demonstrated that aqueous leave extracts stimulated HBsAg population at lower doses (0.5 mg/mL) and also enhanced IgG titre as compared with control and HBsAg treated group. In addition, aqueous leaves extracts of Butea frondosa showed anti-HBsAg titre at higher doses and also showed slightly haemolytic effect in human whole blood. Conclusion: These results suggested that aqueous extract of Butea frondosa may represent viable candidate for effective vaccine adjuvants due to their higher immune response (with respect to IgG titre and proliferation assay) and lower or non-haemolytic effects.